Spherical Solutions of an Underwater Explosion Bubble - Andrew B. Wardlaw; Hans U. Mair (Shock and Vibration)
The evolution of the 1D explosion bubble flow field out to the first bubble minimum is examined in detail using four different models. The most detailed is based on the Euler equations and accounts for the internal bubble fluid motion, while the simplest links a potential water solution to a stationary, Isentropic bubble model. Comparison of the different models with experimental data provides insight into the influence of compressibility and internal bubble dynamics on the behavior of the explosion bubble.